Strategi Pengembangan Kluster Perkebunan Kopi Dan Tebu Untuk Pengembangan Ekonomi Kabupaten Aceh Tengah - Aris Saputra; Ismayani Ismayani; Romano Romano (Jurnal Agrisep, 2015)
ABSTRACT. The purpose of this stady is not indentifiying the cluster and economic strategic development cluster for economic growth supported at Aceh Tengah residence. The study conducted in the Aceh Tengah residence using direct primary data and secondary data. Primary data collection was based of observasing through the objective of stady. Secondary data was taken from literature study and the data from similar institution like Dinas Badan Pusat Statistik Aceh Tengah which has correlation with this study. Analysis that used in this study is the analysis that using Location Quotient (LQ) technical and SWOT analysis. The result of this study show based on Location Quotient (LQ) analysis tekhnical, could identified the comodities that has value LQ1 showed production Existing Condition and Coffe Development Potencial in Linge district, Atu Lintang, Jagong Jeget, Bintang, Lut Tawar, Kebayakan, Pegasing, Bies, Bebesan, Kute Pinang, Silih Nara, Celala, Rusip Antara, while sugar cane just in Ketol District as a strategic comodities for advance development at Aceh Tengah residence. Meanwhile the strategic position of coffee and sugar cane investors placed at aggressive strategic position which supported investors policy, this strategy could be used if the investors has chances and strengths until they could used it coith the strengtht they have, bicause both of it has different value that cunted as positive such about 1,34 and 1,31.